Current dynamics of accumulation and composition of alluvium in the near-channel floodplain of the Oka River (Russia) - A.Yu. Vorobyov; V.A. Krivtcov; A.S. Kadyrov (Учёные записки Казанского университета: Серия Естественные науки)
In 2014–2018, we carried out stationary observations of the lithological characteristics of 263 alluvial sediment samples collected with the sediment traps placed in the near-channel floodplain of the Oka River, about 743–604 km from its mouth. The most intensive sediment accumulation was recorded on the tops and lower parts of the Oka River meanders, with the thickness of the sediment layer up to 50–60 mm/year. Similar sedimentation dynamics were seen in 2018, i.e., during the flood period, when sands and loamy sands were deposited on the channel banks. Fine materials such as silts, silty loams, and clay-silt loams accumulated annually in the backwaters of the Oka River and on the floodplains of its tributaries. The prevalence of fractions sized 0.06–0.01 mm in alluvium after the floods with two low peaks of levels and relatively high turbidity (up to 50–220 g/m3 in 2016–2017) was revealed. The precipitation of sand particles in the backwaters was confirmed only in 2018 as well. In the previous two years, silts and silty and sandy loams accumulated on the channel banks. During the low-energy floods (2014–2015), the fresh sediment layer on all traps did not exceed 11–18 mm; the size of particles was determined by how long the traps remained submerged, as well as by the course of the flood.